Analisis Penanganan Keluhan di Pusat Pengelolaan Pengaduan Masyarakat (P3M) Kota Semarang - Robby Indra Lukman; Ida Hayu Dwimawanti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Public Complaint is the government's effort as a form of fulfilling citizens' rights in managing the aspirations, demands, desires and complaints of the community. Therefore the government is always expected to be able to always improve the quality of services in government institutions, especially in serving the community.In Law Number 25 of 2009 Article 8 paragraph (2) concerning Public Services clearly states that the importance of providing public services to create Public Complaint, through the Public Complaint, the government seeks to facilitate the community by creating a bridge of communication between the government and the public. Public complaints aim at to be able to provide a two-way interactive communication space between the government and the community, thereby facilitating accessibility in providing aspirations, conveying wishes, complaints and demands of the community. To achieve this goal, SP4N LAPOR! as a forum that manages public complaints nationally, the city of Semarang answers the integration of SP4N LAPOR! by establishing the Public Complaints Management Center (P3M) Semarang City through Online Complaint Service named LAPORHENDI. Providing space to express thoughts verbally, in writing or so on the implementation of public services by the government as a form of control efforts to obtain optimal quality services in accordance with applicable regulations, norms and principles. Implementation of Public Complaint Management Center (P3M) Semarang cannot be said optimal yet, because there are still obstacles that have resulted in some being late or even not having a clear process of continuity of complaints. To answer this problem, the author uses a qualitative method approach accompanied by a complaint service quality theory from various views of experts and is used as a foundation to analyze whether Semarang City P3M Service Quality is running properly. This is necessary to examine several influencing indicators by observing, interviewing and reviewing documents in the field that have an impact on the efficiency of the implementation of Complaints Handling at the Public Complaints Management Center (P3M) in Semarang City.